EFFECTIVENESS OF LEGAL PROTECTION FOR VICTIMS OF DOMESTIC VIOLENCE FROM THE PERSPECTIVE OF VICTIMOLOGY AND HUMAN RIGHTS - Ina Maryeli Ginuni; Hiztaful Zahwa Zalita Putri (Papua Law Review, 2026)
This article analyzes the effectiveness of legal protection for victims of domestic violence (DV) through victimology and human rights perspectives. The research uses normative legal methods with a statutory and conceptual approach. The study shows that the Indonesian legal framework recognizes victims' rights to security, health services, confidentiality, assistance, protection orders, legal aid, and reparation. However, protection is not yet fully effective because domestic violence is still treated as a private matter, victims face economic dependence and pressure to reconcile, inter-institutional services are not yet integrated, and reparation often stops after the criminal process. Effectiveness must be measured by the system's ability to stop violence, prevent secondary victimization, ensure victims' participation, and restore their dignity and independence.